Constraint Embankment Construction to Prevent the Collapse of Underground Caves - Zhen Zhang; Zhongda Chen (Advances in Civil Engineering)
Dozens of underground karst caves were found before constructing the Changli highway. The thickness-to-span ratio of nearly half of the caves is less than 0.05, and the greatest ratio is only 0.35, far less than the value demanded by local construction specifications (0.8). The caves located at K50 + 700 and K178 + 800 are by far the only two caves that have become unstable. Only one passive measure was taken when constructing the highway, i.e., building 0.5 m thick continuous reinforced concrete slabs above the embankment; this measure did not contribute to the improvement of the stability of the underground caves. Numerical solutions based on strength reduction and analytical solutions based on the beam hypothesis are used to assess the stability of underground caves. The capacity of an underground cave to bear embankment construction is observed to be proportional to the tensile strength of the rock mass and the square of the thickness-to-span ratio of the cave roof. The tensile strength of the rock mass is ψ times lower than that of the intact rock. The value of ψ is mainly determined by the geological strength index (GSI). To prevent instability of underground caves, the embankment height should be reasonably controlled. However, local construction specifications requiring that the thickness-to-span ratio of underground cave be greater than 0.8 are conservative.